2012
DOI: 10.1523/jneurosci.4749-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Coupling Mediated by Connexin36 in the Primate Retina

Abstract: Photoreceptors are coupled via gap junctions in many mammalian species. Cone-to-cone coupling is thought to improve sensitivity and signal-to-noise ratio while rod-to-cone coupling provides an alternative rod pathway active under twilight or mesopic conditions (Smith et al., 1986; DeVries et al., 2002; Hornstein et al., 2005). Gap junctions are composed of connexins and Cx36, the dominant neuronal connexin, is expressed in the outer plexiform layer. Primate (Macaca mulatta) cone pedicles, labeled with an antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(133 citation statements)
references
References 70 publications
12
119
2
Order By: Relevance
“…These Cx36 plaques were often located on the side or apical surface of cone telodendria or even more distal axonal areas but typically lacked contacts with other cones. These population 1 and 2 Cx36 plaques resembled to sites previously described as coneto-rod GJs in the primate retina (O'Brien et al 2012). In fact, we found that some rod spherules labeled with an antiserum against rod transducin (rTR) displayed a close vicinity to these Cx36 plaques (Fig.…”
Section: Cx36 Colocalization With Photoreceptor Axon Terminalssupporting
confidence: 78%
See 3 more Smart Citations
“…These Cx36 plaques were often located on the side or apical surface of cone telodendria or even more distal axonal areas but typically lacked contacts with other cones. These population 1 and 2 Cx36 plaques resembled to sites previously described as coneto-rod GJs in the primate retina (O'Brien et al 2012). In fact, we found that some rod spherules labeled with an antiserum against rod transducin (rTR) displayed a close vicinity to these Cx36 plaques (Fig.…”
Section: Cx36 Colocalization With Photoreceptor Axon Terminalssupporting
confidence: 78%
“…It has been shown that the human retina, similar to those of other mammalian species, expresses Cx36 both in the IPL and OPL (Söhl et al 2010), and the distribution of immunostained plaques resembled patterns found previously in the mouse, rabbit, rat and the monkey Mills et al 2001;Deans et al 2002;Kihara et al 2006Kihara et al , 2010O'Brien et al 2012;Kovács-Ö ller et al 2014). However, it has been difficult to obtain details on the GJ forming neurons of the human retina due to the postmortem decomposition of available tissue.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…There, Cx36 forms direct functional connections between ganglion cells and amacrine cells (44). Cx36 expression is also present at the intersection of retinal rod and bipolar cells (43). The other likely possibility is paracrine control of islet blood flow arising from products secreted from the islet cells.…”
Section: E328 Connexin 36 Mediates Blood Cell Flow In Isletsmentioning
confidence: 99%